Row spacing and seed rating in two wheat cultivars - Pereira, Luiz Ricardo; Baier, Augusto Carlos; Velloso, José Alberto R. de Oliveira; Santos, Henrique Pereira dos (Pesquisa Agropecuaria Brasileira, 2014)
From 1977 to 1979 in Passo Fundo, Rio Grande do Sul State, Brazil, EMBRAPA/CNPT, the effects of row spacing (10 cm, 20 cm and 30 cm) and seeding rate (300, 400 and 500 viable seeds per m2) on agronomic characteristics of two wheat cultivars were assessed. The effect of year and the interaction of year x cultivar were the main factors that influenced wheat yield. The highest yield was obtained under the narrowest row spacing (10 cm), and was significantly greater than other treatments (20 cm and 30 cm). As seeding rates increased, the number of spikes per plant decreased, but plant population and number of spikes per m2 increased.